Choledocholithiasis and associated hepatopathy in a horse - Montero, Estefania; Henderson, Eileen; Asín, Javier; Uzal, Francisco A. (Brazilian Journal of Veterinary Pathology, 2024)
An 11-year-old bay Warmblood mare with a long-standing history of liver disease was presented to the submitting veterinarian with a three-day history of colic and fever. Initial tests revealed an elevated PCV and leukopenia, accompanied by increased lactate and creatinine levels. Clinically, the horse exhibited swollen limbs and mucosal petechiae. After initial treatment, including intravenous fluids and anti-inflammatory medications, the horse improved briefly but subsequently deteriorated, showing signs of ataxia. Because of the poor prognosis, the horse was euthanized, and a full necropsy was performed.